Intermediate Accounting. - Burns, Thomas J.; Dillon, Ray D. (The Accounting Review, 1981)
Abstract Reviews the book "Intermediate Accounting," by Loren A. Nikolai, Richard G. Schroeder, John D. Bazley and Isaac N. Reynolds.